2017
DOI: 10.1007/s00431-017-2974-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and prognosis of pediatric cryptococcosis in Beijing Children’s Hospital, 2002–2014

Abstract: The majority of cryptococcosis cases in China occurred in children without underlying conditions, causing multiple organ damage. The CNS was the most common site. Patients who had headaches, seizures, or high CSF antigen titers experienced neurological complications or died. What is known: • Cryptococcosis is a rare cause of infection in children. What is new: • This review gives a brief overview over pediatric cryptococcosis in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…In terms of infection profiles of paediatric cryptococcosis, the most frequent (84%) symptom was Cryptococcus meningitis, followed by disseminated cryptococcosis (12%) and skin lesions (4%). The majority of our C. neoformans isolates (80.0%) were recovered from apparently immunocompetent children, and this agrees with previous studies in China (83.6%, 92/110), but differs from studies in USA (20.6%, 13/63) and South Africa (4.4%, 2/45) . Earlier investigations suggested that cryptococcosis primarily occurs in apparently immunocompetent adults in China .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In terms of infection profiles of paediatric cryptococcosis, the most frequent (84%) symptom was Cryptococcus meningitis, followed by disseminated cryptococcosis (12%) and skin lesions (4%). The majority of our C. neoformans isolates (80.0%) were recovered from apparently immunocompetent children, and this agrees with previous studies in China (83.6%, 92/110), but differs from studies in USA (20.6%, 13/63) and South Africa (4.4%, 2/45) . Earlier investigations suggested that cryptococcosis primarily occurs in apparently immunocompetent adults in China .…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, cryptococcosis is rare in children, even those who are HIV‐infected . However, the number of reported cases of cryptococcosis in children has increased in Africa, Europe, South America and Asia, including China . Except for the recent study in South Africa, data on the genotypic diversity and antifungal susceptibility of paediatric Cryptococcus isolates are limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although children account for only 0.9%–2.0% of all cryptococcal cases, the death rate is high, up to 43% ( 47 ). In a 12-year retrospective study in Beijing, 53 pediatric case-patients were encountered, of whom 41 had no underlying conditions ( 48 ). However, the denominator was unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…The associated mortality was described as (20.7%) (LOMES et al, 2016). In China, this disease has affected children without underlying conditions and has shown similar consequences (LIU et al, 2017).…”
Section: Discussionmentioning
confidence: 99%